2022
DOI: 10.1038/s41389-022-00402-w
|View full text |Cite
|
Sign up to set email alerts
|

GSK3β palmitoylation mediated by ZDHHC4 promotes tumorigenicity of glioblastoma stem cells in temozolomide-resistant glioblastoma through the EZH2–STAT3 axis

Abstract: Glioblastoma stem cells (GSCs) are a highly tumorigenic cell subgroup of glioblastoma (GBM). Glycogen synthase kinase 3β (GSK3β) is considered a key hub for promoting malignant phenotypes in GBM. However, the functional relationships between GSK3β and GSCs in GBM are unclear. Here, we found that GSK3β was noted as a substrate for ZDHHC4-mediated palmitoylation at the Cys14 residue, which enhanced GBM temozolomide (TMZ) resistance and GSC self-renewal. Clinically, the expression level of ZDHHC4 was upregulated … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
3
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 14 publications
(3 citation statements)
references
References 36 publications
0
3
0
Order By: Relevance
“…1 b–e). Drug resistance due to alterations in the cell stemness phenotype during cancer treatment has been widely reported 17 19 . The sphere formation assay revealed that individual HGC-27-LR cells exhibited a greater capacity for self-renewal and cellular aggregation into clusters compared to individual HGC-27 cells (Fig.…”
Section: Resultsmentioning
confidence: 99%
“…1 b–e). Drug resistance due to alterations in the cell stemness phenotype during cancer treatment has been widely reported 17 19 . The sphere formation assay revealed that individual HGC-27-LR cells exhibited a greater capacity for self-renewal and cellular aggregation into clusters compared to individual HGC-27 cells (Fig.…”
Section: Resultsmentioning
confidence: 99%
“…612 ZDHHC3 Golgi Palmitoylation of PD-L1 by ZDHHC3 inhibits antitumor immunity in vitro 613 ; palmitoylation of ACE2 by ZDHHC3 is critical for the membrane-targeting of extracellular vesicles secretion 614 ; elevated expression of ZDHHC3 is correlated with poor survival in breast cancer 615 ; high ZDHHC3 levels inhibits synaptic plasticity and memory in high-fat diet (HFD) mice 616 ; ZDHHC3 regulates the infection of primary and latent herpes simplex Virus 1. 617 ZDHHC4 ER, Golgi ZDHHC4 palmitoylates KAI1 and affects its localization, inhibiting angiogenesis 618 ; GSK3β palmitoylation mediated by ZDHHC4 promotes tumorigenicity of GBM stem cells 619 ; palmitoylation of D2R by ZDDHC4 is important for cell surface expression of the receptor. 643 ; the expression of ZDHHC14 is inhibited, leading to increased proliferation and decreased apoptosis in coronary artery disease 644 ; ZDHHC14 is involved in the palmitoylation of SARS-CoV-2 spike protein and contributes to virus entry.…”
Section: Genementioning
confidence: 99%
“…Acting downstream of ERK and AKT, glycogen synthase kinase 3β (GSK3β), a serine/threonine protein kinase, is also considered as a key hub for promoting malignancy of GSCs [ 104 , 105 ]. Zhao et al found that roles of GSK3β are affected by palmitoylation when ZDHHC4 palmitoylates GSK3β at the Cys14 residue [ 106 ]. Mechanistically, palmitoylation of GSK3β negatively affected binding of GSK3β to AKT1 and S6K kinases, thereby releasing the inhibitory roles of AKT1 and S6K on GSK3β.…”
Section: Palmitoylation In Cancermentioning
confidence: 99%